Parastephanellus Enderlein (Hymenoptera: Stephanidae) revisited, with description of two new species from China - Tan, Jiang-Li; van Achterberg, Cornelis; Tan, Qing-Qing; Zhou, Tong; Li, Tao (Zootaxa, 2018)
Two new species of Parastephanellus Enderlein, 1906 (Hymenoptera: Stephanidae) are described and illustrated from China: P. evexus Tan & van Achterberg, sp. n. and P. yixiwui Tan & van Achterberg, sp. n. The male of P. brevicoxalis Hong, van Achterberg & Xu, 2011, is described and the supposed male by Chen et al. (2016) is included in P. evexus. Parastephanellus austrochinensis Belokobylskij, 1995, (former synonym of P. brevistigma Enderlein, 1913) is reinstated. A new key to the species of Parastephanellus Enderlein from China is provided and all species are illustrated.